Well, the solutions manual had:
\(\displaystyle \sum_{k = 2}^\infty \frac{3^{k-1}}{4^{3k+1}}\)
\(\displaystyle \sum_{k = 0}^\infty \frac{3^{k+1}}{4^{3k+7}}\)
\(\displaystyle (\frac{3}{4^7})\sum_{k = 0}^\infty (\frac{3}{4^{3}})^k\)
\(\displaystyle \frac{3}{4^7}*\frac{1}{1 - \frac{3}{4^3}}\)
\(\displaystyle \frac{3}{15616}\).
But \(\displaystyle \sum_{k = 2}^\infty \frac{3^{k-1}}{4^{3k+1}}\) was not the original problem, \(\displaystyle \sum_{k = 0}^\infty \frac{3^{k-1}}{4^{3k+1}}\) was. So, typo maybe? But thanks for the help, at least I know I'm doing these right.